Analysis of Employee Performance Improvement: The Role of Social Exchange Theory - Ginanjar Wira Saputra; Kurniawati Kurniawati; Ahmad Johan; Riza Bahtiar Sulistyan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study aims to examine and analyze the important role of organizational support and training in an effort to improve the performance of Bandung City Transportation Department employees. Organizational support is measured through the dimensions of caring, consideration, problem solving assistance, and the ability to forgive mistakes, while training is measured through training needs, planning, and evaluation. The sample used was 116 employees of the Bandung City Transportation Department. Analysis using multiple linear regression. The results of the analysis show that organizational support and training have a positive and significant impact on employee performance in the aspects of quality, quantity, timeliness and responsibility. The implication is that the transportation agency can consider developing stronger organizational support and optimizing appropriate training programs to improve operational efficiency and effectiveness. Future research could explore other factors that influence employee performance in broader and more diverse contexts.